Modulasi Digital Menggunakan Matlab - Wahyu Pamungkas; Anggun Fitrian Isnawati; Adi Kurniawan (JURNAL INFOTEL, 2012)
In telecommunication systems, the determination of the modulation system is an important method in the process of sending information from transmitter to receiver. In the simulation that is done using QPSK modulation system (Quadrature Phase Shift Keying), 8-QAM (Quadrature Amplitude Modulation), 16-QAM (16-Quadrature Amplitude Modulation) that uses AWGN (Additive White Gaussian Noise) channel in the transmission system uses MATLAB software. The execution of the simulation is aimed to describe how the characteristics of the waveform of each block of the modulator, to add noise in the AWGN channel and demodulator. Performance of modulation system testing is used BER (bit error ratio) method. Looking of the faults of comparison bits results of before and after the transmitted bits by using Monte Carlo simulation model. Testing on this simulation using the input data as much as 10.000 data symbols randomly and the level of Eb/No that is various for each modulation used. Performance results BER with the level of Eb / No at 1 dB of the simulated system modulation on the BER values obtained for QPSK 0.0570, 8-QAM at 0.1085 while the 16-QAM at 0.1582 and then the performance of QPSK modulation is the best. If the Eb / No is increased to 8 dB then the becomes BER QPSK smaller modulation is equal to 0.00035, the 8-QAM BER obtained at 0.0076, while the 16-QAM modulation to be 0.0139